2021
DOI: 10.1111/jocn.16002
|View full text |Cite
|
Sign up to set email alerts
|

The practice of rural and remote nurses in Australia: A case study

Abstract: Aim and Objective To delineate contemporary practice of registered nurses working in rural and remote areas of Australia. Background Despite the implementation of strategies to address challenges reported by rural and remote nurses, concern remains over safety and quality of care, the well‐being of nurses and retention of the nursing workforce. Twenty years on, geographically dispersed nurses still experience scarce human and material resources. Design A multiple case study design was implemented. Methods Nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…However, it is worth noting that ongoing education was a priority for most nurses, consistent with the past literature (Lea & Cruickshank, 2015a). There appears to be a need for greater consideration to be given to how professional development can be adapted to fit the rural context, such as through virtual alternatives to face‐to‐face training (Whiteing et al, 2022), and awareness that cancellation of such training is likely to have long‐term ramifications for satisfaction and retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth noting that ongoing education was a priority for most nurses, consistent with the past literature (Lea & Cruickshank, 2015a). There appears to be a need for greater consideration to be given to how professional development can be adapted to fit the rural context, such as through virtual alternatives to face‐to‐face training (Whiteing et al, 2022), and awareness that cancellation of such training is likely to have long‐term ramifications for satisfaction and retention.…”
Section: Discussionmentioning
confidence: 99%
“…The review identified that higher rural retention was associated with a greater connection with the area (e.g., selection of students who were from rural areas), providing more rural training, and supporting existing rural workers to expand their skills (Russell et al, 2021). This is consistent with research finding that nurses perceive experience as more valuable than education, to facilitate the transition to the unique challenges of rural and remote practice (Whiteing et al, 2022). Interventions that were less effective included regulatory interventions and financial incentives (Buykx et al, 2010; Russell et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To that end, postgraduate education has been found to enhance the ability of nurses to undertake health promotion activities, particularly in response to chronic disease, women's health and education 50 . However, Whiteing et al 34 found that practical experience was perceived as more valuable by registered nurses compared to formal learning opportunities. Muirhead et al 4 highlight the importance of flexible learning opportunities which respond to individual learning needs and setting of the nurse.…”
Section: Discussionmentioning
confidence: 99%
“…A perceived lack of clinical knowledge and broader generalist skill, particularly when working alone, has also been described by several authors. 6,7,33,34 Notably, in her thesis on the experience of locum nurses, Becker 33 described nurses entering the remote setting as '…urban-based professionals with urban-based education' ( 33 p.167). Her findings described confusion about the scope of practice and concern about the level of decision-making that was required.…”
Section: Generalist Knowledge and Skill As A Specialty Practice Areamentioning
confidence: 99%
“…Although there has been extensive research into negative workplace behaviours in the nursing profession, they have been generally in metropolitan settings. Due to the nature of smaller regional locations, health care organizations are often the largest employers in the community (Bushy, 2002 ; Smith et al, 2019 ) and nurses working in these locations have limited employment options (Whiteing et al, 2022 ). Nurses working in regional settings work with limited resources (Smith et al, 2020 ) in an environment where ‘informal social structures predominate’ (Bushy, 2002 , p. 105) and close relationships amongst the community can lead to distortion between professional and personal roles (Bushy, 2002 ; Mills et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%